Analysis on strategic and environmental issues of remanufacturing in India - Ajay Kumar Sinha (Center for Science and Technology, IAIN Surakarta, 2022)
Environmental awareness among masses has created tremendous pressure on government and corporates to preserve our natural resources. Globally, many companies have successfully initiated product recovery operations in their business plans. Remanufacturing is one of the highly profitable and sustainable product recovery options. Many Western countries successfully adopted remanufacturing as an alternate source of revenue generation model. But in India, it is still in nascent stage. In this research, we tried to identify the critical factors in the area of â€œStrategy & Environmentâ€ for the viability of remanufacturing business in India. For this, a questionnaire survey was conducted among Indian manufacturing companies and their responses were analyzed. The sample size of the study consists of 72 responses. Afterwards, the identified factors were ranked based on their criticality in initiating remanufacturing activity. The findings may help Indian government and manufacturing firms to frame proper strategy related to environmental aspect of remanufacturing operations in India.